2013
DOI: 10.1111/ejed.12050
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of Reading and Early Literacy Skills in Schools: a comparison of three European countries

Abstract: This article gives a short overview based on the EU High Level Group of Experts on Literacy (HLWG) report to address issues and challenges in Europe on improving literacy competencies in schools. Furthermore, an analysis is conducted focusing on the promotion of reading and early literacy skills in schools taking into account psychological and institutional learning conditions in three countries (Denmark, Germany, and France) with different outcomes in PIRLS 2011 (Progress in International Reading Literacy Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
(33 reference statements)
1
4
0
1
Order By: Relevance
“…Conversely, Stancel-Piatak, Mirazchiyski, and Desa (2013) found that in three PIRLS participating European countries-Denmark, Germany, and France-a school's emphasis on supporting understanding of a text was not significantly associated with achievement. Importantly, the findings of this study showed that schools' cultural capital was one of the most relevant variables in explaining variation in reading scores.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations
“…Conversely, Stancel-Piatak, Mirazchiyski, and Desa (2013) found that in three PIRLS participating European countries-Denmark, Germany, and France-a school's emphasis on supporting understanding of a text was not significantly associated with achievement. Importantly, the findings of this study showed that schools' cultural capital was one of the most relevant variables in explaining variation in reading scores.…”
Section: Introductionmentioning
confidence: 83%
“…The studies by Martin et al (2013) and Stancel-Piatak et al (2013) confirm that early literacy skills in conjunction with other characteristics of effective schools have a positive influence on achievement. Thus, studies that use a school effectiveness framework suggest that early literacy skills positively impact the PIRLS reading score, but have not addressed the contribution of early home literacy practices or, specifically, of parental book reading.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Ainda em termos globais, os alunos que frequentavam escolas mais bem equipadas e de estatuto socioeconómico mais elevado (escolas de natureza administrativa privada) obtêm melhores desempenhos (Mullis, Martin, Foy, et al, 2017). Esta observação já tinha sido confirmada na Dinamarca, França e Alemanha na edição de 2011 do PIRLS (Stancel-Piątak, Mirazchiyski, & Desa, 2013). Em Portugal, na edição de 2016 do PIRLS, também se observou esta tendência; contudo, quando os recursos educativos em casa (um indicador do estatuto socioeconómico das famílias) são tidos em consideração, o efeito da natureza administrativa (público/ privado) perde a significância estatística.…”
Section: I S C U S S ãO E C O N C Lu S ãOunclassified